PROBIOTIC CORRECTION OF GASTROINTESTINAL TRACT DYSFUNCTIONS IN INFANTS - I.N. Zakharova; N.G. Sugyan (Вопросы современной педиатрии, 2007)
The article discusses the requirements to contemporary probiotics used for children's therapy. the paper presents the dynamic observation data for the most frequent clinic manifestations of gastrointestinal dysfunctions in the infants on the back ground of intestine microbiocenosis correction.Key words: probiotc, prebiotic, symbiotic, gastrointestinal tract dysfunctions, dysbacteriosis.